3D geophysical modelling used for structural interpretation in southern Mali and northeastern Guinea, West Africa - Yossi, Mamadou (My University, 2017)
This study presents the combined processing, integration and inverse modelling of magnetic and gravity data for first-order crustal scale structures in southern Mali and northeast of Guinea. Southern Mali and northeast Guinea form part of the Palaeoproterozoic Baoulé-Mossi domain, which is part of the West African craton (WAC). The current understanding of the geology region is limited to exploration camp-scale studies with limited borehole investigations, and regional interpretations of historic geophysical datasets. In this study geophysical modelling is used to attempt to advance the understanding of the geology at depth. The combination of geophysical methods is an optimization that can support geophysical interpretations and contribute to the determination of the geological and structural characteristics that are important in understanding the subsurface geology. Geophysical inversion modelling broadly resolved geology and structures under thick sedimentary cover (850-1100, thick) that is interpreted as comprising basinal sediments of the Taoudenni basin, or Cretaceous ferricrete. Geological constraints reduced the non-uniqueness, but could not control the quality. Nonetheless, the architecture, geometry and form of structures and dykes were predicted when compared with experimental analogue models as being a reasonable predictive tool for the behaviour of structures and dykes at depth. The use of surface physical properties added more information to the inversion modelling, but was very limited. The enhancement of magnetic and gravity data, using filters, defined tip damage zones for firstorder scale Yanfolila and Banifing shear zones that host gold mineralisation for example, at the Morila gold mine, and Kalana, Kodieran mines and Komana prospects. Second-order structures were also defined including in the tip damage zones of the Siguiri, Fatou and Syama shear zones, and the Manakoro fault, Madina-Yanfolila fault and Madina fault.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the Master degree in Science. 2017.
Keywords: Geophysics; Cratons--Africa, West